Pengaruh Kompetensi Aparat Pengelola Dana Desa, Komitmen Organisasi Pemerintah Desa, dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa - Ni Made Rita Sari; Kadek Dewi Padnyawati (UNHI Press, 2021)
This study aims to determine the effect of village fund management apparatus competence, village government organizational commitment, and community participation on the accountabilityiofvillageifund management in Tabanan District, TabananiRegency. Theisample used in this study were 12 villages in Tabanan District with 96 respondents. The method of determiningithe sampleiusing purposiveisampling, data were collected using a questionnaire. Data were analyzed using Multiple Linear Regression Analysis. Based on the results of this study, it shows that the competence of village fund management officers and the commitment of village government organizations have no significant effect on the accountability of village fund management, while community participation has a positive and significant effect on the accountability of village fund management in Tabanan District, Tabanan Regency.